Examining the Impact of Organizational Culture and E-Human Resource Practices on Employee Commitment and Satisfaction - Alamgir, Muhammad; Ali, Mehak; Ahmed, Zujaj (Annals of Human and Social Sciences, 2024)
This study aims at understanding the role of organizational culture and Electronic Human resources practices on employee’s commitment and Employee Satisfaction. Telecom sector in developing countries has witnessed rapid expansion throughout last decade, this accelerated growth has brought about many challenges one of them is to professionally manage competent workforce and enhancing their commitment. As current study represents a cross-sectional analysis, therefore data was collected at one time from the target population. The responders were professionals with a wide range of expertise and skill sets from various telecom firms employed all over Pakistan. Telecom companies chosen as target population were Ufone, Mobilink, Zong, and Telenor. For that 290 questionnaires were recovered out of 400 distributed, that represents round about 72.5% at the stage of data collection. Regression analysis is used to check the significance of relationship. The findings of this research proved that positive relationships exist between organizational culture and employee commitment, E-human resource practices and Employee satisfaction also between E-Human resources practices and employee’s commitment, whereas, negative relation exist between organizational culture and Employee satisfaction. Despite scholarly consideration in culture and representative's execution, this exploration contributes in collection to the body of the Developing country culture information. Additionally, to the best of the scholar's' nature there was no examination accessible this unique relationship among variables under consideration. Hence, it is recommended that in order to increase employee commitment, companies should make investments in building a solid and supportive organizational culture and a work environment that promotes job satisfaction.